Barriers to Local Language Preservation: Insights from English Teachers in the Luwu Context - Zainuddin, Andi Husni A.; Wisran, Wisran; Taqwa, Nurul Fikriyyah; Amelia, Amelia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The prominence of English as a global lingua franca has posed challenges to the preservation of local languages, including the Luwu language in South Sulawesi, Indonesia. As an essential part of cultural identity, the Luwu language is increasingly marginalized due to the dominance of Bahasa Indonesia and English in formal education. This study examines the challenges faced by English teachers in balancing global linguistic demands with preserving the Luwu language. Using Fishman’s Language Shift and Maintenance and Hornberger’s Continua of Biliteracy as frameworks, this research explores the experiences, perceptions, and strategies of two English teachers in Luwu. The study, conducted through semi-structured interviews, reveals significant challenges, including limited institutional support, a curriculum prioritizing global languages, and the impact of digital media that diminishes students’ exposure to the Luwu language. Teachers employ strategies like integrating Luwu vocabulary into English lessons, fostering both cultural awareness and biliteracy. However, these efforts are constrained by a lack of professional development, resources, and formal guidelines for incorporating local languages into teaching. The findings underscore the importance of institutional and policy support in sustaining local languages. While Indonesia’s muatan lokal policy provides a framework for regional language inclusion, inconsistent implementation and resource gaps hinder its effectiveness. This study advocates for enhanced collaboration among schools, local governments, and communities to develop sustainable language preservation programs. By addressing these challenges, the Luwu language can remain a vital aspect of cultural heritage and identity, ensuring its continuity for future generations.